Aspirin and Sulindac act via different mechanisms to inhibit store-operated calcium channel: Implications for colorectal cancer metastasis - Yu-Shiuan Wang (Elsevier, 2022)
Store-operated Ca2+ channel (SOC)-regulated Ca2+ entry is involved in inflammation and colorectal cancer (CRC) progression, but clinically applicable treatments targeting this mechanism are lacking. Recent studies have shown that nonsteroidal anti-inflammatory drugs (NSAIDs) not only inhibit inflammation but they also suppress Ca2+ entry via SOC (SOCE). Therefore, delineating the mechanisms of SOCE inhibition by NSAIDs may lead to new CRC treatments. In this study, we tested eight candidate NSAIDs in Ca2+ imaging experiments and found that Aspirin and Sulindac were the most effective at suppressing SOCE. Furthermore, time-lapse FRET imaging using TIRF microscopy and ground state depletion (GSD) super-resolution (SR) imaging revealed that SOC was inhibited by Aspirin and Sulindac via different mechanisms. Aspirin quickly interrupted the STIM1-Orai1 interaction, whereas Sulindac mainly suppressed STIM1 translocation. Additionally, Aspirin and Sulindac both inhibited metastasis-related endpoints in CRC cells. Both drugs were used throughout the study at doses that suppressed CRC cell migration and invasion without altering cell survival. This is the first study to reveal the differential inhibitory mechanisms of Aspirin and Sulindac on SOC activity. Thus, our results shed new light on the therapeutic potential of Aspirin for CRC and SOCE-related diseases.